MICROSCOPIC CHANGES IN POST-TRAUMATIC GONARTHROSIS ACCORDING TO DISEASE STAGES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Among all forms of osteoarthritis, gonarthrosis (knee joint osteoarthritis) remains one of the leading causes of disability worldwide. In particular, post-traumatic gonarthrosis is a specific form of secondary osteoarthritis that develops following acute or chronic mechanical injuries to the knee joint. This condition is most commonly observed in young and middle-aged individuals and is clinically characterized by persistent joint pain, restricted mobility, progressive joint deformity, and significant impairment in quality of life and working capacity. The pathogenesis of post-traumatic gonarthrosis involves a complex sequence of degenerative and inflammatory changes in the articular cartilage (hyaline cartilage), synovial membrane, subchondral bone, and periarticular soft tissues. These changes initially begin at the microscopic level, well before the appearance of overt clinical symptoms. Therefore, detailed histopathological assessment of microscopic changes at various stages of the disease is essential for early diagnosis, appropriate staging, and the development of targeted therapeutic strategies. Each stage of post-traumatic gonarthrosis—Stage I (early), Stage II (progressive), and Stage III (advanced)—is associated with distinct microscopic alterations. These include progressive chondrocyte degeneration, disorganization of the cartilage matrix, fibrotic and inflammatory transformations of the synovial membrane, and structural remodeling of subchondral bone with osteophyte formation. Understanding these stage-dependent histological changes is crucial for unraveling the morphogenetic mechanisms of the disease and correlating them with clinical severity. This article presents a comprehensive analysis of the microscopic changes in post-traumatic gonarthrosis across different pathological stages, highlighting their significance in disease progression and clinical management.